Coastal resources degradation in Tangerang, Banten Province: State and management action. Issue 1 (April 2021) - Prismayanti, A D; Mulyana, D; AlAmin, M A; Kurniawan, F; Damar, A; Budiman, M A K; Gunawan, B; Mahardika, S M H
Abstract: Coastal degradation can be determined as mangrove destruction and water quality degradation. Erosion and accretion are the impacts of mangrove destruction in coastal areas. Ecosystem condition and coastal environment destruction were analyzed in Tangerang coastal areas. Soil, mangrove vegetation, and water quality analysis were carried out in this study. Soil quality was analyzed descriptively. Mangrove vegetation and water quality were analyzed with the Important Value Index and STORET Index, respectively. The results indicated that the coastal of Tangerang is damaged both in terms of mangrove and water quality. The causal analysis showed that the damage to the coastal environment in Tangerang is largely influenced by the high amount of plastic, domestic, and industrial waste. Management recommendations that can be carried out on the coast of Tangerang are silvofishery management and mangrove planting right behind the wave breaker.